Category Shift Translation of Noun Phrase in The Cruella Movie Script and Its Translation - Anggi Ratna; Ichwan Suyudi (International Journal of English and Applied Linguistics (IJEAL), 2022)
Each language has its own structure of grammar. The Indonesian language has a different rule of grammar structure from English. As Catford stated, there is a correlation between translation and linguistics. Shifting translation is helpful in learning how a unit of different levels can be brought down to create interesting structures. This paper is aimed to find the category shift of noun phrases in the Cruella movie script and its translation. The method used is a qualitative method. This paper is used Catford’s shift translation theory to analyze the data. As the result, there are 54 data for structure shift, 3 data for a class shift, 7 data for unit shift and 21 data for the intra-system shift. There are also 2 data which represent untranslated noun phrases. The total data found is 87 data.